Legal Protection of Land Ownership Rights In Conflicts With The Kendari Forest Area - Muhammad Takeshi Yusran; Imam Koeswahyono; Indah Dwi Qurbani (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2025)
This study examines the agrarian conflict in Tanea Village, South Konawe Regency, Southeast Sulawesi, which originated from an overlap between community ownership certificates and claims to protected forest areas based on the Decree of the Minister of Agriculture No. 639/Kpts/Um/9/1982 (TGHK). The designation of forest areas without community involvement has created legal uncertainty, restricted access, and the potential for criminalization of farmers. This study uses a socio-legal method with a sociological juridical approach through a normative review of regulations (UUPA, Forestry Law, PP 23/2021, PP 43/2021, Permen LHK 7/2021, MK Decision No. 34/PUU-IX/2011) as well as an empirical study of rights holders, BPN officials, BPKH, and agrarian-forestry experts. The results show that the conflict was triggered by regulatory disharmony, data asymmetry between agencies, dualism of authority, weak evidence of ownership, and the absence of community participation in determining area boundaries. Legal protection efforts can be pursued preventively through negotiation, mediation, and regulatory boundary change mechanisms, or repressively through lawsuits to the State Administrative Court (PTUN). This research emphasizes the importance of community participation in forest boundary inventory, optimizing the One Map Policy, and synchronizing digital data between agencies to achieve fair and balanced legal certainty for both the community and the state.